Theater as phenomenological art and intellectual experience: El escuchador de hielo, by Alfonso Vallejo (XXI Century. Spanish Literature and Culture)
Alfonso Vallejo’s theatre is anti-realist and experimental. The playwright challenges the limits of artistic representation in his works to awaken the social consciousnessof the audience. In El escuchador de hielo (2007), Vallejo uses three postmodern literary conventions –metahtheatre, metalepsis, an intertextuality– to create an artistically, socially, and intellectually provocative and stimulating phenomenon. Using the play Mary Stuart, by Friedrich Schiller, and the torture suffered by Iraqi soldiers in the Abu Ghraib prison as textual and contextual frames, respectively, Vallejo crafts a work that moves the soul, is emotionally and psychologically stirring, and invites the spectators to participate actively in the theatrical event. The result is a play that probes the world in which we live in order to demystify the social facades that we accept as uncontestable truths.
Keywords: postmodern theatre; metatheatre; metalepsis; intertextuality; social consciousness; Alfonso Vallejo